Preserving Islamic Cultural Heritage Through Calligraphy as a Form of Religious Moderation - Muhibuddin Muhibuddin; Yoan Rizki Saputra; Aldi Anwar Kartacasmita; Utik Nurwindah; Yanti Apriani; Ahmad Budi Setiawan (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2021)
Islamic cultural heritage is a very important treasury for Muslims, this is because of its existence as evidence of the advancement of Islamic civilization and the positive side of beauty in life. There are various kinds of Islamic cultural heritage, one of which is the art of calligraphy. This art is widely known and spread in various parts of the world as they spread da'wah from the teachings of Islam. because of its very existence that plays a role as a medium in the writing of the Qur'anic manuscripts and in the learning process, it has a philosophical aspect related to the goals of urgency values in today's religious moderation. Keywords: Preserving; Islamic Cultural Heritage; Calligraphy Art; and Religious Moderation